2017
DOI: 10.3389/fimmu.2017.00517
|View full text |Cite
|
Sign up to set email alerts
|

Ionizing Radiation-Induced Immune and Inflammatory Reactions in the Brain

Abstract: Radiation-induced late brain injury consisting of vascular abnormalities, demyelination, white matter necrosis, and cognitive impairment has been described in patients subjected to cranial radiotherapy for brain tumors. Accumulating evidence suggests that various degrees of cognitive deficit can develop after much lower doses of ionizing radiation, as well. The pathophysiological mechanisms underlying these alterations are not elucidated so far. A permanent deficit in neurogenesis, chronic microvascular altera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
171
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(176 citation statements)
references
References 153 publications
(149 reference statements)
5
171
0
Order By: Relevance
“…Circulus vitiosus is created, so DPS are most probably the consequence of chronic low-level neuroinflammation (17). Our study results match the current hypothesis (16,17).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Circulus vitiosus is created, so DPS are most probably the consequence of chronic low-level neuroinflammation (17). Our study results match the current hypothesis (16,17).…”
Section: Discussionsupporting
confidence: 89%
“…Other studies showed the correlation between hydrocephalus and radiation-induced fibrosis, which disables resorption of cerebrospinal fluid (15). In most cases, hydrocephalus represents the consequence of surgical procedures which involve opening of the ventricular system of the brain (13)(14)(15)(16). In other study results, hydrocephalus appeared in 10% of the patients 10 years after the completion of radiation (15).…”
Section: Discussionmentioning
confidence: 84%
“…The use of radiation therapy in the treatment of a variety of CNS-related malignancies can affect brain structure and function, leading to cognitive deterioration [102]. Radiation used in cancer therapy can also activate the biogenesis and induce exosome secretion from cancer cells [103].…”
Section: Cancer-therapy-derived Exosomes and Cognitive Impairmentmentioning
confidence: 99%
“…Although the precise mechanisms underlying CRCI remain to be established, several studies suggest there is a link between exosomes and CRCI. Exosome biogenesis, its cargo content, function, and activity may be influenced by cancer [97], cancer therapies [93,102], genetics [54,111], age [71], existing comorbidities [112,113], lifestyle [114,115], and environmental [116] factors. Differences in exosomal content (e.g., miRNAs and proteins) and release may exert protective or damaging effects that could alter the brain and CNS function, and cause declining cognitive health in cancer survivors.…”
Section: Potential Implication Of Exosomes In Crci Researchmentioning
confidence: 99%
“…The main pathological manifestation of RBI is cerebral angioedema, which mainly involves the abnormal proliferation of blood vessels in the brain (Lumniczky, Szatmári, & Sáfrány, ; Sona & Marian, ). Among them, vascular endothelial growth factor (VEGF) plays a key role (Andrews et al, ).…”
Section: Introductionmentioning
confidence: 99%